Theoretical and quantitative analysis of cyanosis colouration in newborn - Azmi, Nur Fatihah; Feijs, Loe; Delbressine, Frank (Institute of Advanced Engineering and Science, 2022)
In this paper, the investigation on the occurrence of cyanosis’s blue colouration in newborn babies will be focused on a more detailed version of the oxyhaemoglobin’s (HbO2) and deoxyhaemoglobin’s (Hb) transmission and reflectance spectrum in the blood vessel. A quantitative analysis of cyanosis colour is based on the theory of an observer model of cyanotic skin. The proposed method formed a basis of work of colour changes to be implemented in the future cyanosis baby manikin for baby simulation area. A series of transfer functions were adopted and described by the relationship of the light propagation in human skin. As expected, results showed that the colouration of HbO2 is less saturated (bright red) in comparison to Hb (darker red) and the colouration depends on the HbO2’s and Hb’s reflectance spectrum in the blood. Meaning that, the correct CIEL_a_b_ colour values of cyanosis in real newborn babies will be quantified and later to be implemented in a cyanosis baby manikin. Despite of non-experimental methodology implemented, it is based on putting together existing knowledge from literature. In particular, the database of the absorbance spectra of HbO2 and Hb and the three-cone pigments with three different absorption spectra of the colour receptors in the human retina. The data from Scott Prahl’s Assorted Spectra and the UCL Institute of Ophthalmology’s Colour Matching Functions were retrieved with the spectral values are depending on the light’s wavelength, (_). The results of newborn’s cyanosis colour was obtained and determined both in a two- dimensional International Commission on Illumination (CIE) 1931 xy and a three-dimensional CIE L_a_b_ colour space.